The Utilisation Of Wood Ash As Alkaline Activator For Ambient Cured Geopolymer Concrete - Samsudin, Muhammad Hasnolhadi (2020)
The blended hybrid geopolymer concrete utilising industrial waste ash is a new option of constituent binder material to replace ordinary Portland cement (OPC) concrete. It has a significantly reduced carbon footprint and has a positive impact on the environments. Furthermore, blended hybrid geopolymer concrete proposed to resolve the conventional geopolymer binder issues associated with a high dosage of alkaline activator and elevated curing temperature that hindered the industrial application of geopolymer binder. The study was conducted with the primary aim to hybridise industrial waste ash namely pulverised fuel ash (PFA), ground granulated blast furnace slag (GGBS), high calcium wood ash (HCWA) and silica fume (SF) with suitable alkaline activators to produce binder for concrete. The properties of the blended hybrid geopolymer concrete were assessed based on the fresh properties, mechanical, fluid transport and pore performance. Test specimens were evaluated in terms of standard consistency, setting times, compressive and flexural strength, dynamic modulus of elasticity, ultrasonic pulse velocity, water absorption, capillary absorption, porosity and microstructural performance. The inclusion of PFA at the content of 20-100% by binder weight in ternary blended hybrid geopolymer paste reduced the water demand and significantly prolonged the setting times of ternary blended hybrid geopolymer paste. Meanwhile, the addition of SF by 2-16% in quaternary blended hybrid geopolymer paste shortened the setting times instead.